NAT10 Promotes Osteogenic Differentiation of Mesenchymal Stem Cells by Mediating N4-Acetylcytidine Modification of Gremlin 1 - Zhenbiao Zhu; Xiaowei Xing; Shisi Huang; Yuanyuan Tu (Stem Cells International)
Objective. To investigate the function of NAT10 in mesenchymal stem cell (MSC) osteogenic differentiation and study the mechanism by which NAT10 affects MSC osteogenesis by mediating Gremlin 1 N4-acetylcytidine (ac4C) modification. Methods. Osteogenic differentiation of MSCs was induced, and the osteogenic ability was evaluated with alizarin red S (ARS) and alkaline phosphatase (ALP) assays. The NAT10 expression level during MSC osteogenesis was measured by western blot (WB). MSCs were transfected with lentiviruses to inhibit (Sh-NAT10) or overexpress NAT10 (Over-NAT10), and the osteogenic differentiation ability was assessed by ARS, ALP, and osteogenic gene marker assays. β-Catenin, Akt, and Smad signaling pathway component activation levels were assessed, and the expression levels of key Smad signaling pathway molecules were determined by PCR and WB. The Gremlin 1 mRNA ac4C levels were analyzed using RIP-PCR, and the Gremlin 1 mRNA degradation rate was determined. Sh-Gremlin 1 was transfected to further investigate the role of NAT10 and Gremlin 1 in MSC osteogenesis. Results. During MSC osteogenesis, NAT10 expression, ARS staining, and the ALP level gradually increased. Decreasing NAT10 expression inhibited, and increasing NAT10 expression promoted MSC osteogenic differentiation. NAT10 affected the BMP/Smad rather than the Akt and β-Catenin signaling pathway activation by regulating Gremlin 1 expression. The Gremlin 1 mRNA ac4C level was positively regulated by NAT10, which accelerated Gremlin 1 degradation. Sh-Gremlin 1 abolished the promotive effect of NAT10 on MSC osteogenic differentiation. Conclusion. NAT10 positively regulated MSC osteogenic differentiation through accelerating the Gremlin 1 mRNA degradation by increasing its ac4C level. These results may provide new mechanistic insight into MSC osteogenesis and bone metabolism in vivo.